Uji Aktivitas Antimikroba Ekstrak n-Butanol Madu Hutan (Apis nigrocincta) dari Kabupaten Selayar dengan Metode KLT-Bioautografi - A.Suparlan Isya Syamsu (Sasambo Journal of Pharmacy, 2020)
Preliminary research has been conducted on the antimicrobial activity of n-Butanol extract of forest honey (Apis nigrocincta). This study aims to determine the antimicrobial activity of forest honey from Selayar Regency on the growth of test microbes, using the method of solid dilution with the test microbial Bacillus subtilis, Staphylococcus aureus, Streptococcus mutans, Pseudomonas aeruginosa, Salmonella typhi, Escherichia coli, Vibrio sp, Staphylococcus epidermidis, and Candida albicans against n-butanol extract from forest honey (Apis nigrocincta) at 1 mg/ml. The results obtained showed that n-butanol extract inhibited the growth of bacteria Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus aureus. To estimate the compounds that provide antimicrobial activity, the TLC-Bioautography test is performed. Obtained the best results from the separation of compounds by TLC using Chlorophorom eluate: Acetone (3: 1). The TLC-Bioautographic test results showed that the spots with an Rf value of 0.29 gave activity to Bacillus subtilis, Escherichia coli, and Staphylococcus epidermidis, and gave positive results on the appearance of flavonoid compounds.